Modelo organizacional de la unidad de gestión de riesgos en el Gobierno Autónomo Descentralizado Municipal de San Miguel de Bolívar. - Chico Andrade, Johana Patricia (2021)
The Autonomous Decentralized Municipal Government of San Miguel de Bolívar, an institution that carries out activities to provide public goods and services to satisfy needs, guaranteeing the rights of the population that is established within its jurisdiction. For this reason, this research has focused on conducting an in-depth study of the problems that arise in the San Miguel de Bolívar Municipal GAD, the methodologies used were basic, explanatory, field, bibliographic research. The results obtained in this field research reflect that it is important to carry out an Organizational Model of the Risk Management Unit, describing the tools that organizations have, to provide the development of their administrative functions in order to present in a consolidated, orderly way, permanent and updated information about the attributions, functions, responsibilities and interrelationships of the Risk Management Unit. It is very important to design an Organizational Model of the Risk Management Unit, which helps to inform the members of the Municipal GAD of San Miguel de Bolívar, about the Organizational Structure, job description, in order to reduce the ignorance of the obligations of each one, the duplication of functions, slowness and unimportant complications when carrying out procedures, poor or bad customer service, ignorance of administrative processes, etc. According to the results for each specific objective, the following were obtained: In the first objective, the number of officials the institution has was identified (220 between managers, administrators and workers), in addition, the UGR does not have updated ordinances to improve its actions and functions within the Organizational Model. In the second objective, through the field research carried out (surveys and interviews), flood / landslide threats were identified, these being the ones that affect the Canton more frequently. In the third objective, a proposal for an Organizational Structure was designed, improving the work processes of the Risk Management Unit.